Benefit of Early Initiation of Neuraminidase Inhibitor Treatment to Hospitalized Patients With Avian Influenza A(H7N9) Virus. (23rd October 2017) - Zheng, Shufa; Tang, Lingling; Gao, Hainv; Wang, Yiyin; Yu, Fei; Cui, Dawei; Xie, Guoliang; Yang, Xianzhi; Zhang, Wen; Ye, Xianfei; Zhang, Zike; Wang, Xi; et al.
Abstract : Early neuraminidase inhibitor therapy within the first 2 days of illness can reduce complications, duration of viral shedding, length of stay, and mortality in patients with avian influenza A(H7N9) infection. Abstract: Background: The significance of early neuraminidase inhibitor (NAI) therapy for treating influenza A(H7N9) is currently unknown. Methods: The duration of viral shedding was monitored by reverse-transcription polymerase chain reaction after patients with confirmed H7N9 infection were admitted to the First Affiliated Hospital, Zhejiang University, during April 2013–April 2017. Indices such as the length of hospitalization and mortality were collected, and the correlation between the time of administration of NAI and the severity of disease was systematically analyzed. Results: One hundred sixty patients with confirmed H7N9 infection were divided into 3 groups according to NAI starting time. Three of 20 (15%) patients for whom NAI was administered within 2 days died compared with 12 of 52 (23.1%) patients who received treatment within 2–5 days and 33 of 88 (37.5%) patients who were treated after 5 days ( P < .05). The median durations of viral shedding from NAI therapy initiation was 4.5 days (interquartile range [IQR], 3–9 days) for patients who took antiviral medication within 2 days, which was significantly different from that for patients who took medication within 2–5 days (7.5 days [IQR, 4.25–12.75 days]) or after 5 days (7 days [IQR, 5–10 days]) ( P < .05). We found that the duration of viral shedding from NAI therapy was the shortest in spring 2013 (5.5 days) and the longest in winter–spring 2016–2017 (8.5 days) ( P < .05), showing a prolonged trend. Conclusions: Early NAI therapy within 2 days of illness shortened the duration of viral shedding and improved survival in patients with H7N9 viral infection.